Effect of Repolishing on Color Stability, Translucency, and Surface Roughness of Aged Monochromatic Dental Composites - Abdul-Monem, Mohamed M.; Hussein, Mohamed A.; Abdelrehim, Mona G. (European Journal of General Dentistry, 2024)
Objective This study aimed to test repolishing effect on color stability, translucency, and surface roughness of aged monochromatic dental composite in artificial saliva, tea, mouthwash, and coffee after 1 month, simulating 2.5 years of clinical use.Materials and Methods Omnichroma, a monochromatic dental composite, and Z250 XT a nanohybrid multishade dental composite were used in this study. Specimens (n = 80) from each dental composite were prepared to determine color stability, translucency parameter, and surface roughness after repolishing of aged specimens in artificial saliva, tea, mouthwash, and coffee for 1 month. Scanning electron microscope and laser scanning microscope were used to study surface topography after repolishing. Data was analyzed using analysis of variance, Scheffe test, and independent t-test.Results A significant difference between both dental composites after repolishing in terms of color stability and translucency parameter as that of Omnichroma was higher but sill color changes of Omnichroma were perceptible. There was no difference between both composites in regard to surface roughness after repolishing; however, values of both composites were above the accepted value of 0.2 µm and laser scanning microscope images confirmed these findings.Conclusions Repolishing did not enhance color and surface roughness of aged monochromatic dental composites.
Keywords: monochromatic dental composite; polishing; aged; color; surface roughness; laser scanning microscope